Heterozygous CDKL5 Knockout Female Mice Are a Valuable Animal Model for CDKL5 Disorder. (27th May 2018) - Fuchs, Claudia; Gennaccaro, Laura; Trazzi, Stefania; Bastianini, Stefano; Bettini, Simone; Martire, Viviana Lo; Ren, Elisa; Medici, Giorgio; Zoccoli, Giovanna; Rimondini, Roberto; Ciani, Elisabetta
Abstract : CDKL5 disorder is a severe neurodevelopmental disorder caused by mutations in the X-linked CDKL5 (cyclin-dependent kinase-like five) gene. CDKL5 disorder primarily affects girls and is characterized by early-onset epileptic seizures, gross motor impairment, intellectual disability, and autistic features. Although all CDKL5 female patients are heterozygous, the most valid disease-related model, the heterozygous female Cdkl5 knockout ( Cdkl5 +/−) mouse, has been little characterized. The lack of detailed behavioral profiling of this model remains a crucial gap that must be addressed in order to advance preclinical studies. Here, we provide a behavioral and molecular characterization of heterozygous Cdkl5 +/− mice. We found that Cdkl5 +/− mice reliably recapitulate several aspects of CDKL5 disorder, including autistic-like behaviors, defects in motor coordination and memory performance, and breathing abnormalities. These defects are associated with neuroanatomical alterations, such as reduced dendritic arborization and spine density of hippocampal neurons. Interestingly, Cdkl5 +/− mice show age-related alterations in protein kinase B (AKT) and extracellular signal-regulated kinase (ERK) signaling, two crucial signaling pathways involved in many neurodevelopmental processes. In conclusion, our study provides a comprehensive overview of neurobehavioral phenotypes of heterozygous female Cdkl5 +/− mice and demonstrates that the heterozygous female might be a valuable animal model in preclinical studies on CDKL5 disorder.